A Multifunctional Nanoplatform for Tumor‐Targeted Imaging and Enhanced Ferroptosis Therapy. Issue 4 (19th February 2023) - Zhao, Dan; Wu, Min; Tian, Yanan; Gao, Lu; Wang, Fu
Abstract: With the advantages of ferroptosis therapy (FT) in solving the apoptotic resistance of tumors, a smart strategy based on the combination of glucose oxidase (GOx) and ferroptosis‐inducing nanoagents is proposed to boost the FT. However, most of the nanoagents remain limited in complex synthesis, poor targeting specificity, and unclarified biological mechanisms. Herein, a multifunctional nanoplatform based on fluorescent apoferritin‐gold nanoclusters combined with GOx (AFt‐AuNCs@GOx) is designed for tumor‐targeted imaging and FT. The results show that AFt‐AuNCs@GOx catalyze the generation of toxic ·OH from H2 O2 supplied by GOx. Consequently, AFt‐AuNCs@GOx induce the enhanced ferroptosis effect in 4T1 cells. Additionally, the transcriptome assay of 4T1 cells identifies the differential expression genes related to ferroptosis process after AFt‐AuNCs@GOx treatment. Moreover, with the merit of intrinsic fluorescence, the biodistribution both in vitro and in vivo of AFt‐AuNCs@GOx can be effectively visualized. In vivo evidences reveal that AFt‐AuNCs@GOx have the desired efficacy of FT and excellent biosafety. Overall, the AFt‐AuNCs@GOx nanoplatform offer remarkable advantages in simple architecture, fluorescent imaging, precise targeting, and tumor inhibition. The exploration of the ferroptosis effect and biological mechanisms of AFt‐AuNCs@GOx, as well as its application in tumor therapy, can introduce a new insight into the field of ferroptotic nanomedicine. Abstract : Schematic of a multifunctional nanoplatform based on fluorescent apoferritin‐gold nanoclusters combined with glucose oxidase (AFt‐AuNCs@GOx). Intracellular AFt‐AuNCs@GOx induce an enhanced ferroptosis via the lipid peroxidation generation from the toxic ·OH. AFt‐AuNCs@GOx affect genes expression related to ferroptosis and glutathione metabolism.Therefore, AFt‐AuNCs@GOx integrate imaging, targeting, and ferroptosis therapy for tumor treatment.